Peristiwa Teppo di Kecamatan Tellu Limpoe Kabupaten Sidrap Tahun 2013 - Eri Gustiawan; Patahuddin Patahuddin; Ahmadin Ahmadin (PATTINGALLOANG, 2017)
This is study aims to determine the background of Teppo events and the process of occurrence and impact of Teppo's event in Tellu Limpoe Sub-district of Sidrap Regency. This research is descriptive analysis by using the historical method through stages include Heuristik that collects the source or data as much as possible, source criticism is to determine the authenticity and rehabilitation of sources that have been collected to mngetahui original or not the source, Interpretation is determining the position of fact history professionally, and Historiography or presentation which is a written expression.The results of this study indicate that the occurrence of the Teppo event is the conflict between Teppo community group and Amparita society group which is motivated by social factors, religious factors and juvenile delinquency factor. The incident only lasted for one day on May 23, 2013, starting from the stabbing action conducted by one of the Amparita community to continue at night. As for the impact, among others, in the social field, in the field of economy and education. In the social field, the emergence of fear and hatred between the two groups of people. In the economic field, the cessation of the selling process at Amparita Market and the community owned fields did not manage for a while due to fear and anxiety. In the field of education, the learning process becomes disrupted so that many students and teachers who choose not to go to school or teaching. Keyword : Society Teppo , Teppo Event and District of Tellu Limpoe Sidrap Regency